True or False?
If x , y , z are real numbers such that x + y + z = x y z and x , y , z = ± 1 , then we must also have
1 − x 2 2 x + 1 − y 2 2 y + 1 − z 2 2 z = 1 − x 2 2 x × 1 − y 2 2 y × 1 − z 2 2 z
for all possible values of x , y , z .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
Let A , B , C be real numbers in the range [ 0 , 2 π ) ∪ ( 2 π , π ] such that
tan A tan B tan C = x = y = z .
Note that as an angle θ spans the range [ 0 , 2 π ) ∪ ( 2 π , π ] , tan θ spans the range ( − ∞ , ∞ ) , which is the set of all real numbers, so this substitution is valid.
The given condition rewrites as tan A + tan B + tan C = tan A tan B tan C . We shall prove that this indicates that A + B + C = k π , where k ∈ { 0 , 1 , 2 , 3 } . Manipulating the expression yields
tan A + tan B + tan C tan A + tan B tan A + tan B 1 − tan A tan B tan A + tan B tan ( A + B ) tan ( A + B ) = tan A tan B tan C = tan A tan B tan C − tan C = − tan C ( 1 − tan A tan B ) = − tan C = − tan C = tan ( − C ) .
Since the period of tangent is π , we can say that A + B = − C + k π for some integer k , or A + B + C = k π . Because A , B , C are first and second quadrant angles, the possible values of k are 0, 1, 2, and 3.
Now, we look at the second expression. By the tangent double angle identity, we have
1 − x 2 2 x = 1 − tan 2 A 2 tan A = tan 2 A .
Similarly, 1 − y 2 2 y = tan 2 B and 1 − z 2 2 z = tan 2 C .
We proved that A + B + C = k π previously. Isolating for C yields C = k π − ( A + B ) , and multiplying both sides by 2 gives 2 C = 2 k π − ( 2 A + 2 B ) . Taking the tangent of both sides, and applying the tangent angle sum identity and the identity tan ( 2 k π − θ ) = − tan θ , gives us
tan 2 C tan 2 C tan 2 C tan 2 C ( 1 − tan 2 A tan 2 B ) tan 2 A + tan 2 B + tan 2 C 1 − x 2 2 x + 1 − y 2 2 y + 1 − z 2 2 z = tan ( 2 k π − ( 2 A + 2 B ) ) = − tan ( 2 A + 2 B ) = − 1 − tan 2 A tan 2 B tan 2 A + tan 2 B = − ( tan 2 A + tan 2 B ) = tan 2 A tan 2 B tan 2 C = 1 − x 2 2 x × 1 − y 2 2 y × 1 − z 2 2 z ,
as desired. ■